Effectiveness of Technology Utilization Through Powerpoint Media in Supporting The Learning of Akidah Akhlak at Mts YAPDI Padang Bulan - Riadi, Salamat; Rapono , Muhammad (Journal of Educational Sciences, 2025)
Technology based instructional media, such as PowerPoint, serve as an alternative that teachers can use to present material in a more engaging, interactive, and easily understandable way for students. This study aims to analyze the effectiveness of utilizing technology through PowerPoint media in supporting the teaching of Akidah Akhlak. The research employs a qualitative method with a case study approach, using data collection techniques that include observation, interviews, and documentation. The collected data were then analyzed using the Miles and Huberman technique, which involves data reduction, data display, and conclusion drawing. The results show that the implementation of PowerPoint in Akidah Akhlak learning has led to positive changes in how teachers deliver the material. Previously, the dominant methods were lectures and writing notes on the board; however, with PowerPoint, the material is organized more systematically with key points, images, Quranic verses, and tables. Despite challenges such as limited projector availability, laptop compatibility issues, and classroom lighting, the enthusiasm of both teachers and students remains high. This study demonstrates that the use of PowerPoint media in Akidah Akhlak learning not only helps teachers convey the material more effectively but also enhances students’ comprehension, learning interest, and active participation during the lessons.